THE TEACHER'S TPACK ABILITY INTEGRATED LOCAL WISDOM TO SUPPORT THE ACHIEVEMENT OF PANCASILA STUDENT PROFILE - Pramesti, Diana; Sari, Winda Purnama (Edukasi: Jurnal Pendidikan, 2025)
This study examines teachers” TPACK skills in integrating local wisdom into IPAS learning to develop the Pancasila student profile at SD Muhammadiyah Bangka Belitung. The research method is descriptive qualitative. Data collection techniques are questionnaires, observation sheets, documentation, and interviews. Data analysis techniques use descriptive, quantitative, and qualitative methods. The results showed that teachers had implemented TPACK even though they did not realise the practice was included in the TPACK framework. The highest aspects were PK and TPK, while the lowest were TK and TCK. Local wisdom-based learning successfully stimulates the dimensions of the Pancasila learner profile, such as faith, creativity, independence, and mutual cooperation. However, the achievement of Pancasila learner profile indicators is still in the range of 36-75% due to the lack of teacher training. The recommendation is to increase TPACK training, especially in the TK and TCK aspects, and understanding of the Merdeka curriculum.